2017
DOI: 10.1177/1941738117690847
|View full text |Cite
|
Sign up to set email alerts
|

Overuse Physeal Injuries in Youth Athletes

Abstract: Context:Despite rising awareness of the risks associated with sports participation, overuse injuries continue to increase in youth athlete populations. Physeal injuries are one type of overuse injury exclusive to pediatric populations that are often sustained during athletic practice or competition. Overuse physeal injuries are, in theory, preventable; however, little consensus has been reached surrounding the risk factors, prevention, and treatment strategies.Objective:This systematic review summarizes the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 83 publications
2
50
1
1
Order By: Relevance
“…Likewise, the odds of injury attributable to sports were higher in the school setting compared to nonschool locales. There are several plausible explanations for this finding, such as increased physical fitness in athletes, higher quality equipment, or better trained, more experienced, or more attentive coaches/trainers/supervision in community‐based sports, all of which may lead to fewer serious injuries . Or, it may be the case that school personnel are more likely than other individuals in the community to seek/recommend ED care for injured students (ie, ascertainment bias).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Likewise, the odds of injury attributable to sports were higher in the school setting compared to nonschool locales. There are several plausible explanations for this finding, such as increased physical fitness in athletes, higher quality equipment, or better trained, more experienced, or more attentive coaches/trainers/supervision in community‐based sports, all of which may lead to fewer serious injuries . Or, it may be the case that school personnel are more likely than other individuals in the community to seek/recommend ED care for injured students (ie, ascertainment bias).…”
Section: Discussionsupporting
confidence: 86%
“…There are several plausible explanations for this finding, such as increased physical fitness in athletes, higher quality equipment, or better trained, more experienced, or more attentive coaches/trainers/supervision in community-based sports, all of which may lead to fewer serious injuries. [20][21][22][23] Or, it may be the case that school personnel are more likely than other individuals in the community to seek/recommend ED care for injured students (ie, ascertainment bias). We are unable to test these hypotheses using the current dataset and recommend their investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid changes in physical growth make children particularly vulnerable to overuse injuries, and these types of injuries are increasing among youth populations (Arnold, Thigpen, Beattie, Kissenberth, & Shanley, 2017). A recent study examining visits to a sports clinic for youth ages 5 to 17 found that 53% of visits involved overuse injuries (Stracciolini et al, 2014).…”
Section: Overuse Injuries In Youthmentioning
confidence: 99%
“…[5][6][7][8][9] For early adolescence, when growth velocity peaks (ages 10-16), 10 the most common growth related injuries is apophysitis in the lower limb; Severs in the heel, and Sinding Larsen Johansson and Osgood Schlatter in the knee. 11 All three entities cause long-term pain, decrease in function, and can reduce or completely hinder participation in sports and physical activity. [12][13][14][15][16][17] The most common, Osgood Schlatter, affects 1 in 5 active adolescents.…”
mentioning
confidence: 99%